The diagnosis of limited stage small-cell lung cancer - Sas-Korczyńska, Beata; Wójcik, Ewa; Łuczyńska, Elżbieta; Kulpa, Jan; Korzeniowski, Stanisław (Contemporary Oncology/Współczesna Onkologia, 2008)
Small-cell lung cancer (SCLC) constitutes approximately 20% of all cases of lung cancer. The stage of disease is the most important prognostic factor. The aim of the study was the presentation of diagnostic examinations to identify patients with limited stage (LS) SCLC. The diagnostic procedures were performed in 87 patients with the primary diagnosis of SCLC between 2002 and 2005. The aim of these examinations was qualification of stage of SCLC. Diagnostic procedures included: radiological imaging, bone scan, and morphological and biochemical tests (Coulter blood count, and clinical biochemical liver and renal function tests), and serum levels of markers: lactic dehydrogenase (LDH), neuron-specific enolase (NSE) and pro-gastrin-releasing-peptide (ProGRP). Diagnostic procedures demonstrated the presence of distant metastases in 18 patients (20.69%) and they were classified as extensive stage (ES) SCLC. The most frequent localisation of metastases were: brain (7/18 patients), bones (5/18 patients) and liver (4/18 patients). LS SCLC was confirmed in 69 patients (79.31%). The diagnostic procedures performed before treatment showed: • enlargement of mediastinal lymph nodes in 43 patients (62.32%), • elevated serum levels of: NSE >24.7 ng/ml (in 39 pts. – 56.5%), ProGRP >50 pg/ml (in 54 pts. – 78.3%), and LDH >450 IU/ml (in 12 pts. – 17.4%). Patients with confirmed LS SCLC received concurrent chemo-radiotherapy. During the follow-up period 26 patients (37.7%) developed distant metastases. The most frequent localisation of metastases was: liver (9 pts.), brain (7 pts.), under diaphragmatic lymph nodes (7 pts.), and bones (6 pts.). There were not observed correlations between frequency of dissemination after treatment and elevated serum levels of markers before treatment.